Epidemiology of Human Mycobacterium bovis Disease, California, USA, 2003–2011 - Mark Gallivan; Neha Shah; Jennifer Flood (Emerging Infectious Diseases, 2015)
We conducted a retrospective review of California tuberculosis (TB) registry and genotyping data to evaluate trends, analyze epidemiologic differences between adult and child case-patients with Mycobacterium bovis disease, and identify risk factors for M. bovis disease. The percentage of TB cases attributable to M. bovis increased from 3.4% (80/2,384) in 2003 to 5.4% (98/1,808) in 2011 (p = 0.002). All (6/6) child case-patients with M. bovis disease during 2010–2011 had >1 parent/guardian who was born in Mexico, compared with 38% (22/58) of child case-patients with M. tuberculosis disease (p = 0.005). Multivariate analysis of TB case-patients showed Hispanic ethnicity, extrapulmonary disease, diabetes, and immunosuppressive conditions, excluding HIV co-infection, were independently associated with M. bovis disease. Prevention efforts should focus on Hispanic binational families and adults with immunosuppressive conditions. Collection of additional risk factors in the national TB surveillance system and expansion of whole-genome sequencing should be considered.